Increased CD40L+PD-1+ follicular helper T cells (Tfh) as a biomarker for predicting calcineurin inhibitor sensitivity against Tfh-mediated B-cell activation/antibody production after kidney transplantation. (7th June 2018) - Iwasaki, Kenta; Kitahata, Nana; Hiramitsu, Takahisa; Yamamoto, Takayuki; Noda, Takayuki; Okada, Manabu; Narumi, Shunji; Watarai, Yoshihiko; Miwa, Yuko; Uchida, Kazuharu; Matsuoka, Yutaka; Horimi, Kosei; et al.
Abstract : Calcineurin inhibitors suppress Tfh and donor-specific antibodies in transplant recipients Abstract: It is unclear to what extent the development of follicular helper T cells (Tfh) and de novo donor-specific human leukocyte antigen antibody (DSA) production could be influenced by immunosuppressive agents, particularly calcineurin inhibitor (CNI; cyclosporine or tacrolimus), after kidney transplantation. Here, the effects of immunosuppressive agents on Tfh-mediated B-cell activation and antibody production were investigated. In vitro circulating Tfh (cTfh; memory CD4 + CXCR5 + )/B-cell (CD19 + ) co-culture assays revealed that CNI considerably inhibited cTfh-mediated B-cell activation and IgG antibody secretion through the suppression of IL-21 and IL-2. Both IL-21 and CD40L up-regulated IL-2 receptors (CD25) on B cells, and anti-CD25 antibody induced apoptosis of activated B cells, resulting in the inhibition of IgG production. The frequency of cTfh-expressed CD40L and PD-1 was elevated in patients with de novo DSA 1 year after transplantation. The degree of inhibition by CNI was dependent on Staphylococcal enterotoxin B-induced CD40L + PD-1 + cTfh up-regulation level. Our data demonstrate that CD40L + PD-1 + cTfh could be a marker to implicate individual difference in CNI sensitivity for Tfh-mediated B-cell activation in kidney transplantation.